Lock-up Expiry and Trading Volume Behaviour of Malaysian Initial Public Offering's - Zameni, Abdolhossein; Yong, Othman (International Journal of Economics and Financial Issues, 2016)
The study aims to investigate the lock-up provisions of initial public offering's (IPOs) and its effects on trading volume changes around the lock-up expiry date of Malaysian IPOs by using both the event study methodology and the comparison period returns approach (CPRA) .Unlike the US and the UK, Malaysia's lock-up length is fixed and the number of shares that should be under the lock-up is pre-determined by the Security Commission. The sample comprises 379 Malaysian IPOs, issued from January 2001 to December 2011. The results of the event study methodology and CPRA shows a positive abnormal trading volume at lock-up expiry date for IPO market, except for the ACE Market, Construction and Technology sectors, which is negative and is not consistent with our hypothesis and there is no evidence in previous literatures regarding the significant negative trading volume before and after the lock-up. High trading volume at and around the lock-up expiration is compatible with shareholders' selling due to diversification reasons and wealth recognition and which is also an indication of insider's lack of confidence about a company's future prospect. Significant negative trading volume can be interpreted in a way that insiders of those related boards and sectors do not sell their shares significantly but would rather watch what would happen to the market and are optimistic about Market's future. Furthermore, when we do not adjust the trading volume for the market, the CPRA methodology does not show abnormal trading volume between event window and non-event windows. Keywords: Lock-up provision and Malaysiain IPO market, Trading volume behaviour, Trading board JEL Classifications: G02, G10, G14, G18, G38